Copper and N-Heterocyclic Carbene-Catalyzed Oxidative Amidation of Aldehydes with Amines - Singh, Ashmita; Narula, Anudeep Kumar (Synlett, 2021)
A one-pot two-step oxidative process has been developed for the tert-butyl hydroperoxide mediated transformation of aldehydes and amines into amides catalyzed by copper(I) iodide and an N-heterocyclic carbene. The process is additive-free and does not require the amine to be transformed into its hydrochloride salts. The method is simple and practicable, has a broad substrate scope, and uses economical, feasible, and abundant reagents.
Keywords: N-heterocyclic carbenes; copper catalysis; organocatalysis; aldehydes; amines; amides